Genetic analysis of NR4A2 gene in a large population of Han Chinese patients with Parkinson's disease. Issue 3 (25th July 2012) - Liu, H.; Tao, Q.; Deng, H.; Ming, M.; Ding, Y.; Xu, P.; Chen, S.; Song, Z.; Le, W.
Abstract : Background: NR4A2 gene is a transcription factor crucial for differentiation and survival of midbrain dopamine (DA) neurons, and several variants have been eported to be associated with Parkinson's disease (PD) in the Caucasian population. Methods: To determine whether there is any association of NR4A2 mutation or variation with PD in the Han Chinese population, we performed a genetic analysis of all the exons and exon–intron boundaries in 689 PD patients and 672 controls from mainland China using direct sequencing analysis. Results: We identified four novel variants and two previously reported variants. Two novel variants (exon 2 c.‐20 C>G and exon 3 c.711 C>A) were only found in PD. The others (exon 2 c.‐35 A>G; exon 8 c.1615 G>A; intron 4 IVS4‐16 G>T; and intron 6 IVS6 + 18 insG) were found in both PD and controls at different frequencies. Conclusions: Collectively, our results suggest that NR4A2 may be a susceptibility gene for PD in the Chinese population.